EFFECTS OF INTERNAL CONTROL ON FINANCIAL PERFORMANCE OF SACCOS: A SURVEY OF SACCOS IN NAKURU COUNTY, KENYA. - MARITA, RUTH MWANGO (KABARAK UNIVERSITY, 2016)
Internal control plays an important role in preventing and detecting fraud and protecting the organization's resources, both physical and intangible but fraud is still reported. At the organizational level, internal control objectives relate to the reliability of financial reporting, timely feedback on the achievement of operational or strategic goals, and compliance with laws and regulations. Internal control systems provide guidance for management regarding its evaluation and assessment of internal control over financial reporting. The main objective of the study was to determine the effects of internal controls on financial performance of Saccos focusing on Saccos in Nakuru County. Specifically, the study sought to establish how; control environment, control activities, risk assessment, information and communications and monitoring activities affected the financial performance in Saccos in the area. The study employed the survey research design targeting overall managers, the finance managers and employees in the finance departments of the Saccos. Simple random technique was used during the study to select 276 respondents. Questionnaires were used for the data collection. Data collected was analyzed using both descriptive and inferential statistics with the help of Statistical Package for Social Sciences (SPSS) version 22. The findings revealed that the control environment significantly affected the financial performance of Saccos (β = 0.527), control activities also positively affected the financial performance of Saccos in the area (β = 0.407). However, risk assessment was found to moderately (β = 0.295) affect the financial performance of the Saccos. The findings also revealed that both information and communication (β = 0.585) and monitoring activities (β = 0.669) had the strongest effects on the financial performance of Saccos in the area. Thus, the study brings into limelight the ingredients required for a successful internal control to take place. It can be concluded that the Saccos in Nakuru County generally had functional internal controls in place and these positively affected their financial performance. it is recommended that the Sacco managements properly assign authority and responsibility to qualified individuals; they should also diligently comply with the recommendations of the internal audit report; there is need to avail more risk assessment training to the staff and also equip them with scientific tools to carry out this task. It is also recommended that the Saccos management make themselves more readily available to their staffs since some problems and other emerging issues can be best solved through one-onone communications. Also during monitoring, all redundant procedures and practices should be often replaced to ensure efficiency.
FULL TEXT
Keywords: Internal control, Financial performance, Sacco